"It was like leaving your family": Gentrification and the impacts of displacement on public housing tenants in inner‐Sydney. Issue 2 (16th May 2017) - Morris, Alan
Abstract: In March 2014, the minister responsible announced that all of the approximately 600 public housing tenants of Millers Point and the Sirius Building in inner Sydney are to be moved and the properties sold. Millers Point is probably the oldest public housing area in Australia. The Sirius Building was purpose built for public housing tenants in the late 1970s. The article briefly examines the gentrification process in the Millers Point area. However, the main focus, drawing on six in‐depth interviews with public housing tenants who are still residents in the area and 13 who have moved, is an examination of the impact of the government's removal announcement and the actual displacement of residents. What this article illustrates is that the place attachment of most of the interviewees was profound and the removal announcement and the actual move were devastating. Interviewees spoke of deep sadness and anxiety at the thought of leaving what they considered a unique and genuine community. Residents who had moved told of their isolation and melancholy at having lost their local social network. The research shows that the human cost of policies and not revenue should always be the central consideration.